Eco-Friendly Enterprise: Eco Lego Brick / Norshahirul Syazwan Hairulnazid... [et al.] - Hairulnazid, Norshahirul Syazwan; Roslan, Nur Aina Asyikin; Mohd Diah, Norvanida; Jaafar, Nur Fathiha; Noor Azizan, Azza Zuriahti; Nazri, Nur Fatin Nabilla (2016)
This eco lego brick is a natural, quality, user and maintenance-friendly product, that is durable during all phases of its life cycle.